Pengaruh Orientasi Menggunakan Video Animasi terhadap Pemahaman Pasien Baru di Ruang Rawat Inap: Impact of Animated Video Orientation Towards Understanding Among Newly Admitted Patients - Fhandy Aldy Mandaty; Dian Nur Komalasari; Komsiyah; Ayu Dita Handaningtyas; Achmad Syaifudin; Sumarno (Universitas Ngudi Waluyo, 2026)
New patient orientation is a crucial part of nursing care in the inpatient ward,. Verbal orientation methods are often ineffective due to time constraints, patient condition, and the risk of information not being conveyed optimally. The use of animated video media is expected to improve patient understanding of new patient orientation information. The goal of the study to determine the effect of newly admitted patient orientation using animated video on patient understanding levels in the inpatient ward. This study used a quasi-experimental design with a posttest-only control group design. The sample using a purposive sampling technique. Total sample were 40 respondents, divided into control and intervention respondent. The intervention group received orientation using animated video, while the control group received verbal orientation. Data were collected using a using the Mann-Whitney test. Most patients in the intervention group had a good level of understanding (12 respondents (60%), and most in the control group had a poor level of understanding (8 respondents (40%). The Mann Whitney test results showed a p value = 0.000 (p < 0.05), which means there was a significant effect of the use of animated videos on the level of patient understanding. The use of animated video effectively improved patient comprehension of new patient orientation information in the inpatient ward.